SWOT Analysis of the Bases of Tourism Development in the Kurdistan Region Case Study in Duhok Governorate - األسجاذ امىساغد امدكجِر َادي دنيل اسىاغيل (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The research used SWOT analysis for tourist development elements in Duhok Governorate to classify these elements according to their strengths, weaknesses, opportunities, and threats. The researcher distribute a check list to a sample of (501) responders in Duhok who have the skill to use SWOT analysis and the knowledge about tourist development elements in Duhok Governorate. The sample included university professors, public organization managers, and representatives of parties, NGO, private sector and professional unions. The most important conclusions showed that Duhok has little strengths in tourist development elements;. However, there are many weaknesses. The research also concludes that there are many opportunities to achieve that, and in the same time, many threats face it. The research presents many suggestions in tourist development elements in Duhok governorate, and the most important ones are activating tourism types; and not depending on a kind of common tourism in the governorate, which is the summer tourism, and the importance of developing the infrastrucre in tourism areas.